Microclusters as T Cell Signaling Hubs: Structure, Kinetics, and Regulation - Balagopalan, Lakshmi; Raychaudhuri, Kumarkrishna; Samelson, Lawrence E. (Frontiers in Cell and Developmental Biology, 2021)
When T Cell Receptors (TCR) engages with stimulatory ligands, one of the first microscopically visible events is the formation of microclusters at the site of T cell activation. Since the discovery of these structures almost twenty years ago, they have been studied extensively in live cells using confocal and Total Internal Reflection (TIRF) microscopy. However due to limits in image resolution and acquisition speed, the spatial relationships of signaling components within microclusters, the kinetics of their assembly and disassembly, and the role of vesicular trafficking in microcluster formation and maintenance were not finely characterized. In this review we will summarize how new microscopy techniques have revealed novel insights into the assembly of these structures. The sub-diffraction organization of microclusters as well as the finely-dissected kinetics of recruitment and disassociation of molecules from microclusters will be discussed. The role of cell surface molecules in microcluster formation and the kinetics of molecular recruitment via internal vesicular trafficking to microclusters is described. Finally, the role of post-translational modifications such as ubiquitination in the downregulation of cell surface signaling molecules is also discussed. These results will be related to the role of these structures and processes in T cell activation.